Training on Blended Learning Management with the Assistance of Google Suite to Enhance Integrated Classroom Management - R. Ati Sukmawati; Novan Alkaf Bahraini Saputra; Muhammad Hifdzi Adini; Mitra Pramita; Yogie Prayoga; Muhammad Iman Rizqullah; Abdul Rasyied; Nabila Najmi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Technology-based learning has been widely applied at various levels because it offers benefits and convenience for teachers and students. One example is a combination of offline and online learning called blended learning. It's just that teachers, both the concept and how to apply it, do not fully know this application; therefore, it is necessary to conduct training on the concepts and steps of application and supporting technology for blended learning for teachers. Mastery of applications in the Google Suite environment (Google Classroom, Google Forms, Google Docs, Google Slides, and Google Sheets) is important to manage blended learning optimally. This community service program aims to help teachers improve their competence in mastering IT for learning through training activities and mentoring in blended learning management utilizing Google Suite. The Participatory Action Research (PAR) method used in this activity provides space for participants to be active in learning the concepts and supporting technologies of blended learning. SMP Negeri 3 Banjarmasin is willing to be a partner in this activity. The needs of participants are the main foundation for the implementation of this training. Participants consisted of 24 people who came from various service periods and fields. The evaluation results of this activity revealed that 100% of participants believed it was easy to apply blended learning with the help of Google Suite. In addition, 92% of participants thought using Google Suite would make asynchronous classes more interesting. This activity succeeded in increasing the competence of participants in mastering IT, which was integrated into learning.